2000
DOI: 10.1002/1522-2683(200011)21:17<3673::aid-elps3673>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of silver stain and SYPRO Ruby Protein Gel Stain with respect to protein detection in two-dimensional gels and identification by peptide mass profiling

Abstract: Proteomic projects are often focused on the discovery of differentially expressed proteins between control and experimental samples. Most laboratories choose the approach of running two-dimensional (2-D) gels, analyzing them and identifying the differentially expressed proteins by in-gel digestion and mass spectrometry. To date, the available stains for visualizing proteins on 2-D gels have been less than ideal for these projects because of poor detection sensitivity (Coomassie blue stain) or poor peptide reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 0 publications
1
66
0
2
Order By: Relevance
“…SYPRO Ruby was selected as the staining method for the HCP studies. SYPRO Ruby was compared to silver stain for the detection of proteins in sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS–PAGE) by Lopez et al () and the study demonstrated both had very similar sensitivity. In addition, SYPRO Ruby also presented advantages over silver stain including a broad linear dynamic range and enhanced recovery of peptides from in‐gel digest for mass spectrometry studies.…”
Section: The Complexity Of Host Cell Protein Populationsmentioning
confidence: 99%
“…SYPRO Ruby was selected as the staining method for the HCP studies. SYPRO Ruby was compared to silver stain for the detection of proteins in sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS–PAGE) by Lopez et al () and the study demonstrated both had very similar sensitivity. In addition, SYPRO Ruby also presented advantages over silver stain including a broad linear dynamic range and enhanced recovery of peptides from in‐gel digest for mass spectrometry studies.…”
Section: The Complexity Of Host Cell Protein Populationsmentioning
confidence: 99%
“…After electrophoresis, the protein gel can be stained for visualisation, quantification and comparison. Apart from the most commonly used Coomassie brilliant blue and silver stain for global protein detection, fluorescent dyes such as Sypro Orange, Sypro Red or Sypro Ruby, which provide additional benefits such as high sensitivity, simplicity and wide dynamic range 12,13 . Using size‐ and charge‐matched fluorescent CyDyes, two‐dimensional fluorescence difference gel electrophoresis (2‐D DIGE) technique has been developed recently, which provides a quantitative dimension to the traditional 2D PAGE technique 14,15 .…”
Section: What Are the Proteomic Technologies?mentioning
confidence: 99%
“…Hundreds to thousands of individual protein spots can be visualized depending on protein loading conditions and staining methodology [54][55][56]. Standard staining approaches include Coomassie Brilliant Blue [54] and silver [57,58], as well as a variety of fluorescent dyes [58][59][60][61]. One of the most powerful comparative ways of analyzing proteomes is fluorescence difference in-gel electrophoresis [62], which uses 2-CyDye or 3-CyDye systems to differentially label proteins belonging to dissimilar protein mixtures prior to gel electrophoretic separation [63][64][65].…”
Section: Gel Electrophoretic Protein Separa-tionmentioning
confidence: 99%